Exploring the Potential Use of Natural Products Together with Alkalization in Cancer Therapy - Masahide Isowa; Reo Hamaguchi; Ryoko Narui; Hiromasa Morikawa; Toshihiro Okamoto; Hiromi Wada (MDPI AG, 2024)
Cancer treatment is a significant focus in medicine, owing to the increasing global incidence of cancers. Patients with advanced cancers that do not respond to conventional therapies have limited options and an unfavorable prognosis. Consequently, researchers are investigating complementary approaches to conventional treatments. One such approach is alkalization therapy, which aims to neutralize the acidic tumor microenvironment (TME) by increasing its pH level. The acidic TME promotes inflammation, tumor progression, and drug resistance. Alkalization therapy has been demonstrated to be effective for various cancers. In addition, natural products, such as triterpenoids, parthenolides, fulvic acid, Taxus yunnanensis, and apple pectin have the potential to alleviate symptoms, maintain physical fitness, and improve treatment outcomes of cancer patients through their anti-inflammatory, antioxidant, and anticancer properties. In this review, we focus on the effects of alkalization therapy and natural products on cancer. Furthermore, we present a case series of advanced cancer patients who received alkalization therapy and natural products alongside standard treatments, resulting in long-term survival. We posit that alkalization therapy together with supplementation with natural products may confer benefits to cancer patients, by mitigating the side effects of chemotherapy and complementing standard treatments. However, further research is warranted to validate these clinical findings.